FOOD INTAKE PROFILE OF CELIAC DISEASE PACIENTS IN THE GASTROPEDIATRIC CLINIC OF UNIVERSIDADE FEDERAL DE MINAS GERAIS, BRAZIL - Marina Magalhães de Sousa-; Magda Bahia; Romero Tavares Alves; Francisco José Penna (Universidade do Estado do Rio de Janeiro, 2014)
Introduction: Celiac disease is an autoimmune disease triggered by the presence of wheat gliadin and similar proteins in barley and rye in the diet of susceptible individuals. Since the treatment of this disease is following a gluten-free diet it is very important to keep nutritional monitoring of these individuals. Non-adherence to the diet can lead to nutritional deficiency. There are few studies in Brazil addressing the nutritional aspects of celiac disease patients. Objective: To assess the dietary intake of patients with celiac disease. Methods: We evaluated 31 patients with celiac disease and 31 healthy individuals from three to 23 years; a convenience sample was used. For analysis of food intake we carried food frequency questionnaire, dietary records and 24-hour dietary recall. Results: Food intake, calorie and lipids consumption was higher in the study group. Carbohydrate intake was higher in the control group. Despite the difference in the amount ingested, the proportion of individuals, in both groups, who achieved the daily requirement for vitamins and minerals in accordance with the selected IDRs showed no statistical difference. Conclusion: The gluten-free diet was not harmful to the eating habits of the study participants. Diet composition of patients with celiac disease was similar to the diet of the control group. No statistical differences were found between the proportion of subjects with ideal, below or above intake for vitamins and minerals in both groups. DOI: http://dx.doi.org/10.12957/demetra.2014.9660